2013
DOI: 10.1111/1475-679x.12032
|View full text |Cite
|
Sign up to set email alerts
|

Auditor Choice in Politically Connected Firms

Abstract: We extend recent research on the links between political connections and financial reporting by examining the role of auditor choice. Our evidence that public firms with political connections are more likely to appoint a Big 4 auditor supports the intuition that insiders in these firms are eager to improve accounting transparency to convince outside investors that they refrain from exploiting their connections to divert corporate resources. In evidence consistent with another prediction, we find that this link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
143
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 261 publications
(189 citation statements)
references
References 159 publications
14
143
2
5
Order By: Relevance
“…On the one hand, politically connected firms are more inclined to hire a Big 4 auditor (Bliss & Gul, ; Guedhami, Pittman, & Saffar, ) compared with their nonconnected counterparts, so that stakeholders perceive their financial reporting to be more credible. Guedhami et al () further showed that this relationship is stronger for politically connected firms that have concentrated ownership structures, as well as for connected firms conducting business in countries with poor institutional infrastructures. Khan, Mihret, and Muttakin () found that politically connected firms in Bangladesh appoint high‐quality auditors to reduce high agency costs.…”
Section: Determinants Of Auditor Choicementioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, politically connected firms are more inclined to hire a Big 4 auditor (Bliss & Gul, ; Guedhami, Pittman, & Saffar, ) compared with their nonconnected counterparts, so that stakeholders perceive their financial reporting to be more credible. Guedhami et al () further showed that this relationship is stronger for politically connected firms that have concentrated ownership structures, as well as for connected firms conducting business in countries with poor institutional infrastructures. Khan, Mihret, and Muttakin () found that politically connected firms in Bangladesh appoint high‐quality auditors to reduce high agency costs.…”
Section: Determinants Of Auditor Choicementioning
confidence: 99%
“…Studies reveal that auditor choice is affected by the complex interplay of political connections and other factors; for example, (i) ownership structures of politically connected firms (Cheng et al, ; Guedhami et al, ; Habib et al, ; Liu et al, ); (ii) the different types of political connections (Cheng et al, ; Habib et al, ); (iii) the significance of political connections (Liu et al, ); (iv) group affiliations (Guedhami et al, ) and related party transactions (Habib et al, ); and (v) the institutional infrastructures of different countries (Guedhami et al, ). However, there might be other incentives and opportunities that cannot be isolated from these models.…”
Section: Determinants Of Auditor Choicementioning
confidence: 99%
“…The crony capitalism and political patronage literature suggests that PCFs are plagued by severe agency problems (Boubakri, Guedhami, Mishra, & Saffar, ; Chaney, Faccio, & Parsley, ; Guedhami, Pittman, & Saffar, ; Houston, Liang, Lin, & Ma, ). PCFs can evade market discipline, accountability, and transparency in corporate dealings by not seeking financing from the equity market, since the government can influence banks to offer highly competitive financing rates to PCFs (Chaney et al, ; Khwaja & Mian, ; Leuz & Oberholzer‐Gee, ) .…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Chaney et al () documented that PCFs are not unduly concerned with their reported lower earnings quality, since they are not penalized with higher cost of debt . This emboldens PCFs to implement opaque financial reporting to siphon corporate resources, through third‐party‐related transactions and self‐dealing activities (Boubakri et al, ; Chaney et al, ; Guedhami et al, ). Thus, from the perspective of agency problems, auditors will increase their audit effort in PCFs to mitigate risks of lower earnings quality, fraudulent reporting, and material misstatements.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Following prior studies, we use three variables to measure a firm's commitment to higher levels of audit verification. Given research indicating that Big 4 auditors provide higher quality audits, and that the decision to hire a Big 4 auditor represents a firm's commitment to better financial reporting quality, both in the USA and globally (Choi & Wang, 2007; Francis, Maydew, & Sparks, ; Francis & Wang, ; Guedhami, Pittman, & Saffar, ), our first measure of audit commitment is the choice of a Big 4 auditor ( Big4Auditor ) made by a firm in a given year . In addition, following previous studies (e.g., Ball et al, ; Chen et al, ), we use the amount of total actual audit fees ( AuditFee ) and excess audit fees ( ExcessFee ) to measure a firm's commitment to higher levels of audit verification.…”
Section: Data Sample and Empirical Modelsmentioning
confidence: 99%